Improving Students’ Arabic Vocabulary Acquisition through a Flashcard-Assisted Drill Method - Laura Rohmatul Azkiya; Wulan Indah Fatimatul Djamilah; Ely Mufidah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Low students’ learning motivation and limited vocabulary (mufrodat) mastery remain persistent challenges in Arabic language learning, leading to low student engagement and overall learning outcomes. This study aims to improve students’ vocabulary mastery through the implementation of the drill method supported by flashcard media. The study employs a descriptive qualitative approach, with the researcher acting as the instructor in the Arabic language learning process involving 32 seventh-grade students. Data were collected through classroom observations, interviews, and questionnaires to obtain a comprehensive understanding of the teaching and learning process and students’ responses. The results indicate that the systematic application of the drill method combined with flashcard media enhances students’ vocabulary retention, pronunciation accuracy, and learning enthusiasm. Flashcards function as visual stimuli that support memory reinforcement, while repetitive practice through the drill method deepens students’ understanding of vocabulary. In addition, students demonstrate increased motivation, self-confidence, and active participation during classroom activities. Therefore, the integration of the drill method and flashcard media proves to be an effective and enjoyable learning strategy for improving vocabulary mastery in Arabic language learning and can serve as an alternative approach for teachers in developing vocabulary instruction.